2020
DOI: 10.1029/2019jd031515
|View full text |Cite
|
Sign up to set email alerts
|

The Stationary Banding Complex and Secondary Eyewall Formation in Tropical Cyclones

Abstract: 89 GHz passive microwave satellite data are used to develop a five year climatology of the incidence and morphology of the stationary banding complex in tropical cyclones and quantify changes in convective morphology prior to secondary eyewall formation. The stationary banding complex is shown to be present in 39% of passive microwave overpasses. Morphology varies substantially between tropical cyclones, with crossing angles ranging from 0.19° to 61.78° and azimuthal extents from 0.29 π to 4.02 π radians. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
3
6
3
Order By: Relevance
“…This result is seemingly inconsistent with Vaughan et al. (2020), which found that the VWS is significantly lower in the SBC group. Indeed, Vaughan et al.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…This result is seemingly inconsistent with Vaughan et al. (2020), which found that the VWS is significantly lower in the SBC group. Indeed, Vaughan et al.…”
Section: Discussioncontrasting
confidence: 91%
“…Similar results were also evidenced in an observational study by Vaughan et al. (2020) in which a stationary banding complex (SBC) in TC's outer core was seen within 6 hr before SEF in about 80% concentric eyewall cases. Vaughan et al.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations